Leccinum molle (Bon) Bon and Leccinum vulpinum Watling: the first study of their nutritional and antioxidant potential - Reis, Filipa S. (2016)
This work presents the chemical profile of two edible species of mushrooms from the genus Leccinum: Leccinum molle (Bon) Bon and Leccinum vulpinum Watling, both harvested on the outskirts of Bragança (Northeastern Portugal). Both species were prepared and characterized regarding their content in nutrients (i.e., free sugars, fatty acids and vitamins), non-nutrients (i.e., phenolic and other organic acids) and antioxidant activity. To the best of our knowledge, no previous studies on the chemical characterization and bioactivity of these species have been undertaken. Accordingly, this study intends to increase the available information concerning edible mushroom species, as well as to highlight another important factor regarding the conservation of the mycological resources--their potential as sources of nutraceutical/pharmaceutical compounds. Overall, both species revealed similar nutrient profiles, with low fat levels, fructose, mannitol and trehalose as the foremost free sugars, and high percentages of mono- and polyunsaturated fatty acids. They also revealed the presence of bioactive compounds, namely phenolic (e.g., gallic acid, protocatechuic acid and p-hydroxybenzoic acid) and organic acids (e.g., citric and fumaric acids) and presented antioxidant properties.